Parallel implementation of a geometrical reconstruction interface algorithm over openFOAM(R) - Márquez Damián, Santiago (2017)
Even when the Piecewise-Linear Interface Calculation algorithm is a well established tech- nique for interphase reconstruction related to the Volume of Fluid method and is implemented in sev- eral privative codes for arbitrary meshes, no freely-distributed version is available to the date for the OpenFOAM(R) libraries suite. This works presents implementation details of this technique over Open- FOAM(R) to be used on parallel platforms. Much of them are related with the underlying numerics and the fundamental requirement of local and global conservativeness. Two main aspects are covered in this work: the computation of face fluxes by intersection of swept volumes and interface cells and the calculation of curvatures in each cell. While the first aspect does not present much difficulties, curva- tures computation results in an interesting case in how to manage a problem not well suited for message passing parallelization.